Dokumentacja medyczna elementem bezpieczeństwa pracy ratownika medycznego - Susło, Robert; Paplicki, Mateusz; Kozakiewicz, Marzena; Drobnik, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Emergency medicine serves providing both pre-hospital medical services directly at emergency site and during transportation, and hospital emergency services at hospital emergency wards that result from previous rescue activities. Filling in medical documents is akey element ofparamedic’s activities indifferent of employing institution; as in Poland they are kept predominantly in paper form a cyberattack risk is low in this case. Keeping correct and proper medical records plays key role in ensuring both patient’s medical safety and paramedic’s formal and legal safety, including cases of suspected medical error. It is troublesome because ofcharacteristics of paramedic’s job that include in particular multitasking, time andresponsibility pressure and resulting in stress.
Keywords: prawo medyczne; dokumentacja medyczna; ratownitwo medyczne